PENERAPAN METODE DISKUSI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VB SDN 005 BUKIT TIMAH KECAMATAN DUMAI SELATAN - Nurti Tinambunan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
The background of this study is the low learning outcomes of IPS students of grade V B SDN 005 Bukit Timah with average student learning outcomes of 56.00. The purpose of this study is to improve the learning outcomes of IPS through the application of discussion methods. This research is a class action research, the subject of this research is the students of grade VB SDN 005 Bukit Timah with the number of 32 students. This research was conducted in two cycles with four stages: planning, implementation, observation and reflection. The results showed that the discussion method can improve the learning result of IPS. This is evidenced by the average acquisition of learning outcomes in the first cycle of 70,78 with good category, in the second cycle of 75,31 with good category.